(untitled) (Gestión y Gerencia, 2020)
Descriptive field research whose purpose is to analyze the investment project research modality for the construction of knowledge from the perspective of technological innovation. The population consisted of 14 Industrial Engineering students. It was developed in three phases: investment projects’ demanded requirements verification through a checklist, projects characteristics description, and finally, knowing students’ opinion regarding the investment projects. An instrument validated by experts with dichotomous questions was applied. The results showed that investment projects as a research modality generate new technological innovation knowledge where market, technical and economic-financial studies are carried out, they seek to provide solutions, optimize lines, search for new, more profitable, lower-cost products and manufacturing with procurement materials in Venezuela.